Volume 2: Coal, Biomass and Alternative Fuels; Combustion and Fuels; Oil and Gas Applications; Cycle Innovations 2001
DOI: 10.1115/2001-gt-0048
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of a Liquid-Fuel Jet in an Unsteady Cross-Flow

Abstract: This paper describes an experimental study of a fuel jet in an unsteady cross flow as part of a program to evaluate active control of combustion instabilities that involve acoustic / spray coupling. The results provide insights into the different physical mechanisms through which the jet and cross flow interact and the degree to which acoustic velocity fluctuations modulate liquid jet mixing, penetration and spray distribution. They also provide a means of evaluating the effectiveness of fuel fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…( 0 represents the bulk velocity) is equal to about 35% in the work by Anderson et al [19], whereas values between 5% and 20% are reported by Song et al [21]. Whereas Anderson et al [19] obtained a huge oscillation of the liquid column linked with an influence on the spatial distribution of the spray particle number density, Song et al [21] observed very little influence of the excitation on the jet trajectory but a periodic variation of the droplet size distribution. More recently, Sharma and…”
Section: Simulation Des Instabilités De Combustion Générées Dans Les mentioning
confidence: 86%
“…( 0 represents the bulk velocity) is equal to about 35% in the work by Anderson et al [19], whereas values between 5% and 20% are reported by Song et al [21]. Whereas Anderson et al [19] obtained a huge oscillation of the liquid column linked with an influence on the spatial distribution of the spray particle number density, Song et al [21] observed very little influence of the excitation on the jet trajectory but a periodic variation of the droplet size distribution. More recently, Sharma and…”
Section: Simulation Des Instabilités De Combustion Générées Dans Les mentioning
confidence: 86%
“…Depending on the amplitude and frequency of the air velocity oscillations and the averaged momentum flux ratio q between the two fluids, the liquid jets may cyclically impact the inner or the upper wall of the injection system forming a liquid film which is re-atomized at the edge of the diffuser. Such coupling between the air crossflow and the atomization of a liquid jet was shown by Anderson et al (Anderson, Proscia & Cohen 2001), Song and Lee (Song, Ramasubramanian & Lee 2013) and Sharma and Lee (Sharma & Lee 2018).…”
Section: Introductionmentioning
confidence: 64%
“…The actuator used to force the jet is a spinning valve developed at UTRC [1]. Air supply is provided to a plenum inside a rotating drum (which is connected to a motor spool) with 40 holes around the periphery; see schematic in Fig.…”
Section: Spinning-valve Actuator and Azimuthal Mode Generationmentioning
confidence: 99%
“…The experiments reported in this paper were performed in two campaigns. In the first one, the actuator system was reused from the original development [1] so that its utility for jet noise mitigation could be established preliminarily. In particular, the injector was essentially a flattened tube with the flat edge aligned parallel to the nozzle trailing edge (see Fig.…”
Section: Spinning-valve Actuator and Azimuthal Mode Generationmentioning
confidence: 99%
See 1 more Smart Citation